Predictors of Low Uptake of Prenatal Tetanus Toxoid, Reduced Diphtheria Toxoid, and Acellular Pertussis Immunization in Privately Insured Women in the United States. Issue 4 (April 2017) - Butler, Anne M.; Layton, J. Bradley; Li, Dongmei; Hudgens, Michael G.; Boggess, Kim A.; McGrath, Leah J.; Weber, David J.; Becker-Dreps, Sylvia
Abstract : OBJECTIVE: To examine the uptake of prenatal tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) immunization among pregnant women in the United States. METHODS: Using MarketScan data, we conducted a historical cohort study among pregnant women with employer-based commercial insurance in the United States who delivered between January 1, 2010, and December 31, 2014. We examined temporal trends of uptake, predictors of uptake, and timing of Tdap immunization. RESULTS: Among 1, 222, 384 eligible pregnancies in 1, 147, 711 women, receipt of prenatal Tdap immunization increased from 0.0% of women who delivered in January 2010 to 9.8% who delivered in October 2012 (the date of the recommendation by the Advisory Committee on Immunization Practices for Tdap during every pregnancy) to 44.4% who delivered in December 2014. Among women who received Tdap during pregnancy, the majority were immunized between 27 weeks and 36 6/7 weeks of gestation per the Advisory Committee on Immunization Practices recommendation. In multivariable analyses among women who delivered between November 2012 and December 2014, rates of prenatal Tdap immunization were lower for women younger than 25 years of age (eg, 20–24 compared with 30–34 years rate ratio [RR] 0.83, 95% confidence interval [CI] 0.85–0.88), with other children (eg, three compared with zero children: RR 0.86, 95% CI 0.84–0.88), residing in the South compared with the Midwest (RR 0.81, 95% CI 0.80–0.82), or with emergency department visits in early pregnancy (RR 0.93, 95% CI 0.92–0.95). The proportion of pregnant women who received prenatal Tdap increased with increasing gestational age at birth. CONCLUSION: By the end of 2014, fewer than half of pregnant women in the United States were receiving prenatal Tdap immunization. Implementation and dissemination strategies are needed to increase Tdap coverage among pregnant women, especially those who are young, have other children, or reside in the South. Abstract : Fewer than half of pregnant women are receiving guideline-recommended tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis immunization.Supplemental Digital Content is Available in the Text.